Indexing in the REDIB database. - Figueira, Karina (Brazilian Journal of Implantology and Health Sciences, 2020)
It is with great satisfaction that we inform our readers and collaborators that BJIHS is now in one of the largest and most prestigious scientific database in Spain, REDIB. REDIB (Ibero-American Network of Innovation and Scientific Knowledge) is a platform for aggregating scientific and academic content in electronic format produced in the Ibero-American sphere, related to it in a broader cultural and social sense and geographically not restrictive. REDIB has a clear vocation to promote technological innovation in editorial production tools. These facilitate access, dissemination and improvement of scientific production generated in the countries within its reach, especially in the various languages. The recipients of this information are both the academic community and society in general, as well as those responsible, managers and scientific policy analysts. The Internet guarantees the global reach of this information. Karina Silva Figueira Editor to BJIHS